Kajian Kitab Al Arba’in An Nawawiyah - Silvia Riskha Fabriar (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2020)
The hadith is one of the guidelines for Muslims. Every Muslim wants to live according to the teachings of Islam as exemplified by the Prophet Muhammad. The hadiths of the Prophet were compiled by the scholars into a book (book) so that it would be easy for the next generation to learn. Al Arba'in An Nawawiyah is one of the books of the Prophet's hadith collection which is popular among the people. Through this study, the author wants to learn the description, methods and systematics of the preparation of the book Al Arba'in An Nawawiyah. Al Arba'in An Nawawiyah contains authentic hadith which discusses worship and muamalah and is classified as a book of takhrij.